Preparation and characterization of novel edible matrices based on alginate and whey for oral delivery of iron. (January 2020) - Durán, Emerson; Churio, Osmaly; Arias, José Luis; Neira-Carrillo, Andrónico; Valenzuela, Carolina
Abstract: Matrices composed of blends of alginate/whey and iron sources as ferrous sulfate (FS) and bovine spray-dried blood cells (BC) were prepared by ionic gelation, characterized, and tested in vitro as a carrier for the oral delivery of iron. The major components of these matrices were carbohydrates and proteins, and their iron concentrations ranged from 3 to 34 mg per matrix. By using scanning electron microscopy, Fourier transform infrared spectroscopy, X-ray diffraction and differential scanning calorimetry, these matrices were deemed stable and we observed that iron was successfully incorporated into them. In terms of resistance, we observed that it decreased along with the increasing concentration of FS for each of the matrix formulations. Our results indicate that these matrices released low concentrations of iron under gastric conditions simulated in vitro (2.4–11.1%), whereas iron was released massively under intestinal conditions (83–100%). We also observed that matrices were gradually degraded under intestinal conditions. Consequently, our results indicate that these matrices could be used as a viable strategy for oral iron supplementation. Graphical abstract: Image 1 Highlights: Matrices were prepared based on alginate/whey to carry different types of iron. These matrices contained iron concentrations ranging from 3 to 34 mg per matrix. These matrices released small amounts of iron under gastric conditions in vitro. These matrices released most of their iron under intestinal conditions in vitro. These matrices may become a fun and novel kind of oral iron supplement.